The Aesthetics of Taste: Eating within the Realm of Art - Koczanowicz, Dorota (Brill, 2023)
When does eating become art? The Aesthetics of Taste answers this question by exploring the position of taste in contemporary culture and the manner in which taste meanders its way into the realm of art. The argument identifies aesthetic values not only in artistic practices, where they are naturally expected, but also in the spaces of everydayness that seem far removed from the domain of fine arts. As such, it seeks to grasp what artists - who offer aesthetic as well as culinary experiences - actually try to communicate, while also pondering whether a cook can be an artist.